The Effectiveness of Using Story Mapping Technique Towards Students’ Narrative Text Reading Comprehension Achievement - Elpiza, Erna; Manalullaili, Manalullaili; Amalia, Hariana (Jadila: Journal of Development and Innovation in Language and Literature Education, 2024)
This study aims to find out whether the use of the story mapping technique could improve students’ reading comprehension achievement and there was significant difference between the students who were taught by using the story mapping technique and those who were not. This research applied a quantitative approach in pretest and posttest nonequivalent design. From 494 students of population at the eighth grade of MTS N 1 Palembang and the number of the sample in this research was 66 divided into experimental and control used convenience sampling. The technique of data collection was reading test. To analyze the data, the researcher used paired sample t-test to find out whether there was a significant improvement in reading comprehension achievement after being taught using Story Mapping Technique. It was found the t value was 14.832, the t-value was higher than critical value of t-table (1.66901). It can be stated that there was significant improvement in reading comprehension achievement after being taught using Story Mapping Technique. In addition, the result of the independent sample t-test showed that the value of the t-test was 4.168, the t-value was higher than critical value of t-table (1.66901) it meant the alternative hypothesis was accepted and the null hypothesis was rejected. It can be concluded that there was a significant difference in students’ achievement in narrative reading for the students who were taught using the story mapping method and those who were not. Therefore, story mapping technique can provide solution to improve students narrative reading comprehension significantly.